Metastatic thyroid carcinoma presenting with spinal cord compression. - Hassan, H. A.; Ab. Hamid, Suzana (Hong Kong Academy of Medicine Press, 2010)
Metastatic follicular thyroid carcinoma presenting with spinal cord compression is rare. We describe a 69-year-old woman who initially presented with gradual onset of bilateral lower limb weakness and numbness for 3 months. Her magnetic resonance image revealed extradural spinal cord compression at the T3/T4 level by a right chest wall mass, which was histologically proven to be follicular thyroid carcinoma.